Mixing Individual Incentives and Group Incentives: Best of Both Worlds or Social Dilemma? - Barnes, Christopher M.; Hollenbeck, John R.; Jundt, Dustin K.; DeRue, D. Scott; Harmon, Stephen J. (Journal of Management, 2011)
Equity theory emphasizes making distinctions between individual contributions to teams and then recognizing these with differentiations in rewards. However, social interdependence theory emphasizes maximizing cooperation in teams by compensating members equally. Several researchers have advocated offsetting the limitations of individually based incentives and group-based incentives by mixing the two. However, the authors contend that this puts team members in a social dilemma, leading them to focus on the individually based component. The authors find that in comparison to group-based only incentives, mixed individual/group incentives lead team members to perform faster but less accurately and focus on their own taskwork to the detriment of backing up behavior.